Феномен Картала: динамика смысла - Бруяко, И.В. (Материалы по археологии Северного Причерноморья, 2019)
Об историко-географическом феномене Картала, который предопределён стратегическим положением памятника, в литературе сказано было вполне достаточно . Можно лишь в очередной раз констатировать, что такое особенное (в чём-то уникальное) положение местонахождения Картала обеспечивал Дунай – природный ландшафтный рубеж, который время от времени обретал статус демаркационной линии – этнокультурной (археологической) в преистории и историко-культурной (геополитической) в историческую эпоху. Феномен Картала не был явлением статичным, а обладал известной динамикой. Именно обусловленность такой динамики и предполагается обсудить в этой работе. In the article some features of functional existing of the site near the place of cross through Danube in its lower part (Isakcha – Orlovka area). We are talking about the multilayer settlement (hillfort) Kartal. An attempt was made to show that appearance here the settlement in the concrete historical, or pre-historical period was not accidental. In the ground of the Kartal phenomenon, there was the one universal pattern. In each case, the appearance of the settlement was inspired by geopolitical circumstances and occurred, while the Danube acquired the status of a strategic line (cultural-historical, military-political), which divided the various cultural communities, civilizations, states. When the Danube flow existed inside some homogeneous archaeological, cultural space, in this case the Danube has been missing geopolitical status and became simple landscape and geographical unit with the functions of inner communication line. The necessity in the site in Kartal in these cases was not.